Custo de capital e investimentos corporativos: um estudo de empresas brasileiras de capital aberto - Xavier, Rodolfo Weber Silva (2019)
Investment decisions that generate wealth for shareholders and maximize firm value usually need to consider the cost of capital to be employed. By proposing an analysis of the cost of capital influence on firms corporate investment it is possible to provide information on how investment decisions are influenced by the cost of capital. In this study the model proposed by Frank and Shen (2016) is used to evaluate the impact of the cost of capital on firms corporate investment within Brazilian companies traded at Sao Paulo Stock Exchange (B3). The sample is composed of 399 companies with annual accounting data between 2005 and 2018. The econometric model relates cost of capital and cash flow with investments and uses regressions with panel data. For the calculation of the Weighted Average Cost of Capital (WACC), two models are used for the components of cost of equity: General Capital Asset Pricing Model (GCAPM) and Implied Cost of Capital (ICC). The ICC estimate is based on Hou et al. (2012), which uses regression techniques from accounting data to forecast earnings, and from these forecasts estimate the implied cost of capital. We conclude that the WACC has significant and negative impact on investments. In addition, we conclude that when the WACC is estimated using the ICC, it has a greater impact on the association with the investment, and the ICC can better capture the relation between the cost of capital and investments in Brazilian companies. The approach adopted in this study allow us to understand the application of the ICC calculation model from accounting data, different from usual models based on analysts’ forecasts. This methodology is a viable and interesting alternative to estimate the implied cost of capital in developing markets, characterized by greater information asymmetry and few companies covered by market analysts.